Factors Influencing the Choice to Advise for or against COVID-19 Vaccination in the Physicians and Dentists of an Italian Region - Eleonora Marziali; Alberto Lontano; Luca Regazzi; Andrea Paladini; Leonardo Villani; Giovanna Elisa Calabrò; Gianfranco Damiani; Patrizia Laurenti; Walter Ricciardi; Chiara Cadeddu (Vaccines, 2022)
Healthcare workers (HCWs), particularly physicians, are a relevant and trusted source of information for patients, especially when health-related choices such as vaccination are concerned. Between July and November 2022, we administered a web-based survey to physicians and dentists living in the Latio region of Italy to explore whether their background might affect their willingness to recommend the COVID-19 vaccination to their patients (RCVtoPat) and their relatives (RCVtoRel). We performed a multivariable logistic regression to study the association between the two outcomes (RCVtoPat and RCVtoRel) and their potential determinants in our sample (n = 1464). We found that being a dentist, an increasing fear of COVID-19, and having been previously vaccinated against flu are positively associated with both RCVtoPat and RCVtoRel, while a better self-rated knowledge of COVID-19 vaccines is associated only with RCVtoRel. No role was found for age, sex, civil status, education level, information sources, previous SARS-CoV-2 infection, and chronic diseases. A sub-group analysis of physicians alone (n = 1305) demonstrated a positive association with RCVtoRel of being specialized in diagnostic/therapeutic services and a negative effect on RCVtoPat of being trained in general practice. We provide useful insights about the factors that should be addressed to ensure HCWs exert a positive influence on their patients and communities.